Application of immunocorrection in complex pregnovative preparation for IVF in patients with adenomiosis 1-2 degrees - I. I. Kucenko; V. A. Avakimyan; E. I. Kravcova; O. V. Tomina (Медицинский вестник Юга России, 2017)
Purpose: to evaluate the role of immunocorrection in the complex pregravidational preparation for IVF for the restoration of the endometrial implantation potential in patients with grade 1-2 adenomyosis. Materials and methods: By simple randomization, the patients were divided into two groups: 1 group of 45 patients — complex pregravidational preparation. (PGP), including reception of dienogest at a dose of 2 mg per day for 3 months and intravenous administration of deoxyribonucleinate at a dose of 75 mg, group 2 — 43 patients — GWP, including reception of dienogest at a dose of 2 mg per day for 3 months. Th e control group (group 3) consisted of 45 healthy fertile women. Initially, and in dynamics, LIF, LIF-R, IL-6, IL-10 in cervical mucus were determined by the method of enzyme immunoassay. Results: A comparative analysis of pre-gravitational preparation for the IVF cycle in patients with infertility associated with adenomyosis of 1-2 degrees and the implantation potential of the endometrium as much as possible reduced against this background. Isolated use of dienogest and complex therapy (dienogest + deoxyribonucleate sodium) was used. Th e analysis of the indicators took into account the infl uence of various methods of pregravidational preparation on the local cytokine balance (IL, IL10) and indicators characterizing the implantation potential of the endometrium (LIF and LIF-R). Conclusion: complex pregravidational preparation provides a full recovery of the implantation factor of the endometrium, which is confi rmed by an increase in the frequency of biochemical and clinical pregnancy.